Oral communication strategies of pre-university Malaysian Chinese students / Liang Kaizhu - Liang, Kaizhu (2016)
Communication in a language other than a person’s mother tongue is difficult (Khan & Victori i Blaya, 2011; Kongsom, 2009; Somsai & Intaraprasert, 2011; Teng, 2012). Communication strategies play an important role in language acquisition as it could offer non-native speakers the ability to deliver effective communication while speaking in English (Dörnyei & Scott, 1997; Oxford & Burry-Stock, 1995). The purpose of this study was to identify the most frequently used Oral Communication Strategies (henceforth OCSs) by pre-university Malaysian Chinese students and the relationship between oral English language proficiency (henceforth OP) and OCSs. Once the OCSs were identified, the possible reasons for using them by students with different OP were investigated. This study used a descriptive research method where it started with a quantitative approach (questionnaire survey) and followed by a qualitative approach (structured interview). The questionnaire of OCSI (Oral Communication Strategy Inventory) developed by Nakatani (2006) was adapted to collect data from 60 pre-university Malaysian Chinese students at a matriculation college, among whom 15% (n=9) were interviewed. MUET (Malaysian University English Test) was used to classify students into different proficiency levels, such as proficient level (Band 5), satisfactory level (Band 4) and modest level (Band 3) in the study. The results found that the participants are highly aware of the usage of OCSs in speaking and they can be regarded as high strategy users. Moreover, a significant and sizeable association between OP and students’ usage of OCSs was found by using Spearman correlation coefficients. Finally, students’ possible reasons for using certain existing OCSs were identified through structured interview. The suggestions for future research were put forward.